EXPERIMENTS USINGBASED VIRTUAL LAB PHET SIMULATION IN LEARNING PHYSICS ON PARABOLIC MOVEMENT MATERIALS - Trieana S Tuhusula; Burana Pattana; Efania Randai; Dionizius R Wateriri; Auldry F Walukow (Universitas Negeri Medan, 2020)
Parabolic motion is a physics learning material that requires experimentation for its application, so that in the era of the Revolution 4.0 requires something to innovate, so technological progress is very much needed. Experiments using virtual labs are one example of physics learning that is relevant to the current situation. The aim is to determine the use of PhET as an alternative to laboratory space and to study the concept of parabolic motion material theoretically, as well as mathematically to calculate the maximum height, farthest distance with the influence of mass, initial velocity and changes in elevation angles in parabolic motion material. In obtaining data according to research objectives, experimental techniques, observation and documentation were used. The instrument used is a